ANALISIS HUBUNGAN TINGKAT KEPATUHAN DAN KEBERHASILAN PENGOBATAN PASIEN TUBERKULOSIS PARU DEWASA FASE INTENSIF DI RSUD DR. SOEDARSO PONTIANAK - Rahmania, Alfina; Susanti, Ressi; Purwanti, Nera Umilia (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Background: Tuberculosis is an infectious disease that need to be treated properly and in the long term. One of the therapeutic outcome’s factor is medication adherence by patients. Aimed : This aims of study to determine the relationship of adherence to therapeutic outcome in the RSUD dr. Soedarso Pontianak. Method : The type design of this research used observasional retrospective with cross-sectional analysis. The tools used in this research are medical records and the MMAS-8 questionnaires to measure the level of medication adherence in intensive phase of pulmonary tuberculosis patients. Correlation between scores adherence and therapeutic outcome were analyzed by Kolmogorov-Smirnov test. The subject in this research are patients diagnosed positive acid-fast bacillus. Result : The result from 24 pulmonary tuberculosis patients that conform the inclution criteria, there is a significant correlation (p<0,05) between medication adherence of patients and intensive phase of therapeutic outcome in patients with pulmonary tuberculosis. Keywords: Tuberculosis, medication adherence, acid-fast bacillus, Therapeutic Outcome